Biogeochemical properties of seawater measured from the icebreaker Shirase during the 55th Japanese Antarctic Research Expedition in the austral summer, 2013–2014 - TAKAHASHI, Kunio T.; IIDA, Takahiro; TAKAMURA, Tomomi R.; ODATE, Tsuneo (2015)
P(論文) Fig. 1, 2 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_183_0004_2014.doc Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_183_0001_2014.xls Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v002/nipr_parc_183_0002_2014.xls Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_183_0003_2014.xls departmental bulletin paper